Idea scenografii aktywnej w twórczości Danyły Lidera (1917–2002) - Bobula, Joanna (Studia Ukrainica Posnaniensia, 2025)
The work of the visual artist, scenographer and pedagogue Danylo Lider occupies a special place in the history of Ukrainian scenography. Working with the stage space was for Lider the only way to express individual, independent and creative thinking, especially in the years when the prevailing doctrine of socialist realism imposed strict boundaries on art. The postulates of creativity propagated by this Ukrainian artist were based on the idea of active scenography, which, in contrast to flat and unambiguous illustration (decoration), dynamizes the space and allows for the creation of a complex image. Lider created conscious artistic projects, deeply thought-out and, above all, harmonizing with his worldview (expressed in terms of a big and small world).